Evidence for Whom? A Systematic Review of Eligibility Criteria in RCTs of Anti-VEGF for Neovascular Age-Related Macular Degeneration - Andreas Arnold-Vangsted; Emil Alexander Rosenørn; Emilie Theresa Sørrig Butler; Rodrigo Anguita; Rita Serrano Anjos; Lasse Jørgensen Cehofski; Vibeke Christensen; Lorenzo Ferro Desideri; Jakob Grauslund; Javad Nouri Hajari; Musa Yasin Kaya; Oliver Niels Klefter; et al. (AJO International)
Purpose: To summarize the eligibility criteria used in randomized controlled trials (RCT) of intravitreal anti-VEGF treatments for neovascular age-related macular degeneration (AMD). Design: Systematic review. Methods: A search of 12 literature databases was conducted on 15 April 2024. RCTs of intravitreal anti-VEGF for the treatment of neovascular AMD in treatment-naïve eyes were identified. Data on the eligibility criteria for visual function, disease definition and stage, ocular comorbidities, systemic comorbidities, demographics, and other factors not included in other categories were extracted. Results: A total of 49 eligible studies were included in this review, which together included 26,995 eyes of 26,995 patients. We identified a range of eligibility criteria on areas of visual function (minimum 18–50 ETDRS letters; maximum 69–78 ETDRS letters), disease definition and stage (FA only vs. multimodal approach), ocular and systemic comorbidities (most frequent exclusion criteria across studies were any history of the following: intraocular surgery, diabetic retinopathy, panretinal photocoagulation, glaucoma, and myopia), demographics, as well as a miscellaneous category with other topics. Studies employed a set of criteria so stringent that it could be questioned to which extent patients included were generalizable to real-world patients with AMD. Conclusions: RCTs of anti-VEGF treatments for neovascular AMD employ stringent eligibility criteria, which in consequence may reduce the generalizability of findings to real-world populations.